Research on seismic vulnerability of buildings and seismic disaster risk: A case study in Yancheng, China. (May 2020) - Zhou, Junxue; Li, Sha; Nie, Gaozhong; Fan, Xiwei; Deng, Yan; Xia, Chaoxu
Abstract: Seismic vulnerability assessment of buildings has scientific guiding significance for mitigating seismic disaster risk, making the decision-makers in prioritization their limited resources for risk reduction in the administrative units from which they are responsible for. This paper has carried out the seismic vulnerability assessment of buildings in Yancheng area. There are four typical building types in this study area which are civil structure, pure masonry structure, brick-concrete structure, frame structure. Based on the typical building structural components, eight first-level vulnerability indicators (vertical load-bearing component, ring beam, mortar of infilled wall, roof or floor structure, foundation, height of building, nonstructural component, anti-seismic joint or other anti-seismic measures) are selected to build the seismic vulnerability index system of buildings. Next, an Analytic Hierarchy Process mathematical model is developed to access the weight value of first-level and second-level vulnerability indicators. And the seismic vulnerability assessment model of building has been established. Furthermore, considering the seismic hazard, population exposure and seismic vulnerability of buildings, the seismic disaster risk distribution of Yancheng area is finally determined. The distribution map of seismic disaster risk provides a solid scientific and technological support for the government to investigate the potential risk points.